Sector spillovers in credit markets - Collet, Jerome; Ielpo, Florian (Journal of Banking & Finance, 2018)
Cross-sector volatility spillovers can both threaten the financial stability of credit markets and the diversification of a credit bond portfolio. In this article, we measure cross-sector volatility spillovers, casting light on their intensity in the US-denominated investment grade bond universe. We find that volatility spillovers are high in the US credit market and that the insurance, goods and energy sectors have been net contributors to these shocks over the 1996–2017 period. A structural analysis of the spillover history based on a three-regime multivariate VAR Markov Switching model is then proposed. It highlights that with different volatility regimes come different volatility spillover structures: the insurance and goods sectors are volatility spillover sources during crisis periods. However, according to our estimates a large portion of spillovers are non-recurring and therefore difficult to anticipate.